Comparison of saddle contoured metal matrix and pre-contoured self-adhesive matrix in composite resin class II restorations; an in vivo study - Sarwar, Nosheen; khokhar, Sheharyar Akhtar (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate composite class II restoration proximal contacts and contours by comparing saddle-contoured metal matrix and pre-contoured self-adhesive matrix system. Method: The randomised controlled trial (NCT05414656) was conducted at the Department of Operative Dentistry, School of Dentistry, Shaheed Zulfiqar Ali Bhutto Medical University, Pakistan Institute of Medical Sciences, Islamabad, Pakistan, from May to October 2022, and comprises the patients having supra-gingival class II cavities. They were randomised into class II restoration with saddle-contoured matrix band group A, and restoration with pre-contoured self-adhesive matrix group B. The tightness of proximal contacts was evaluated using the Fédération Dentaire Internationale criteria and the quality of proximal contours was assessed using clinical and radiographic examination. Data was analysed using SPSS 16. Results: Of the 60 subjects, 42(70%) were females and 18(30%) were males. The overall mean age was 38.03±15.33 years. There were 30(50%) subjects in each of the 2 groups. The highest restoration was needed in the upper premolar 20(33.3%). The tightness of proximal contact was not significantly different between the groups (p=0.94). Clinical examination for production of good contours was higher in group A compared to group B, but the difference was not significant (p>0.05). Conclusion: There was no significant difference between saddle-contoured metal matrix and pre-contoured self-adhesive matrix for composite class II restoration proximal contacts and contours. Clinical Trial Link: https://clinicaltrials.gov RCT (NCT05414656) Key Words: Dental restoration, Composite resin, Dental caries, Matrix bands.